SATISFACTION TOWARD LEARNING MANAGEMENT SYSTEM: EXTENDED SCALE OF EDUCATIONAL SYSTEM QUALITY - Hendrick Hernando; Afina Hasya (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: Consideration against educational system quality in the context of the learning management system has increased during the pandemic period. An inconsistent finding concerning the influence of educational system quality on satisfaction has been identified. To fill this gap in the existing literature, this study aims to extend the educational system quality scale and examine its influence on students’ satisfaction.